Pain and ketoprofen: what is its role in clinical practice? - F. Fischer; M. Colombo; M. Bagnasco; L. Lanata; F. Atzeni; P. Sarzi- Puttini; M. D'Imporzano (PAGEPress Publications, 2011)
Patients fear pain because it causes considerable suffering, and clinicians may not handle it appropriately because they fail to understand it (1). The International Association for the Study of Pain (IASP) defines it as "... is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage" (2). Individual patients perceive it differently, depending on the context of the stimulus, their previous experience, and their current psychological and physical condition. Furthermore, painful stimuli cannot be ignored, disturb behavioural and cognitive activities, and give rise to anxiety and/or depression (3, 4). Acute pain is one of the most frequent reasons for consulting a doctor in all parts of the world (5), and is often associated with already distressing...